Reducing Disturbance in Manufacturing System with Discrete-event Simulation - Razman, Mat Tahar; Fazeeda, Mohamad; Norhanom, Awang (2011)
This study aims to present a modelling of production flow in HICOM automotive industry in Malaysian using discrete-event simulation (DES). The purpose of the study is to reduce disturbance or constraints in a manufacturing plant operation problem using discrete-event simulation (DES) model. This was based on data collection in Painting Shop (PS) in production manufacturing plant. Case experiences indicate that combining data analysis with DES is beneficial in identifying and reducing disturbance or constraints in manufacturing system. The computer-based integrated approach successfully reduces the risk of inefficiency cause of these problems in operation. The computer simulation enables the reduction of disturbance and constraint in existing capacity suggested improvement in productivity than existing production operation. The study makes a business case that process improvement through reduction of disturbance and constraint can be effectively accomplished with the integrated approach of using widely available inexpensive and user-friendly computer-based tools